Long-Term Porcine Retina Explants as an Alternative to In Vivo Experimentation - Weller, Maria; Müller, Brigitte; Stieger, Knut; Justus Liebig University Giessen (My University, 2024)
Purpose: The porcine retina represents an optimal model system to study treatment approaches for inherited retinal dystrophies owing to close anatomical similarities to the human retina, including a cone enriched visual streak. The aim of this work was to establish a protocol to keep explants in culture for up to 28 days with good morphological preservation. Methods: Two to four retina explants per eye were obtained from the central part of the retina and transferred onto a membrane insert with the photoreceptors facing down. Different medium compositions using Neurobasal-A medium containing 100 or 450 mg/dL glucose and combinations of fetal calf serum, B-27 with or without insulin and N-2 were tested. We developed a tissue quality score with robust markers for different retinal cell types (protein kinase C alpha, peanut agglutinin and 4′,6-diamidino-2-phenylindol). Results: Retinae were kept until 28 days with only little degradation. The best results were attained using Neurobasal-A medium containing 100 mg/dL glucose supplemented with B-27 containing insulin and N-2. For an easy preparation process, it is necessary to minimize transport time and keep the eyes on ice until dissected. Heat-mediated decontamination by the butcher has to be avoided. Conclusions: Using a standardized protocol, porcine retina explants represent an easy to handle intermediate model between in vitro and in vivo experimentation. This model system is robustly reproducible and contributes to the implementation of the 3R principle to minimize animal experimentation. Translational Relevance: This model can be used to test future therapeutic approaches for inherited retinal dystrophies.
Keywords: ddc:610